Tinjauan Yuridis Sosiologi Terhadap Kasus Balap Liar di Kota Kupang (International Forum of Researchers and Lecturers, 2023)
Juvenile delinquency in Kupang City is very diverse, one of which is illegal racing. Teenagers who indulge in this behaviour do not care about the safety and security of themselves or other road users. The purpose of this research is to analyse the juridical sociology review of illegal racing cases in Kupang City. This type of research is empirical juridical research. The type and source of data used are primary data, namely data obtained directly from the research location through direct interviews with respondents. The data is analysed descriptively qualitative. The results of this study indicate that the factors that cause a lot of illegal racing in Kupang City are sociological factors consisting of environmental factors and betting factors. Psychological factors consisting of adolescent personality factors and hobby factors. Efforts made by investigators against the perpetrators of illegal racing in Kupang City are carried out in two ways, namely, preventive efforts and repressive efforts. It is hoped that teenagers have legal awareness and it is hoped that police officers, especially traffic police, will be more assertive in sanctioning teenagers who often commit traffic violations, especially illegal racing violations, so that there is a deterrent effect for the perpetrators.